2010
DOI: 10.1002/masy.201000029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of an Organoclay, Triphenylphosphate, and a Mixture of Both on the Degradation and Combustion Behaviour of PC/ABS Blends

Abstract: Summary: Polycarbonate Acrylonitrile‐Butadiene‐Styrene blends (PC/ABS) with flame retardants Triphenyl Phosphate (TPP), nanoclay and their mixtures were prepared in a twin‐ screw extruder. The morphological properties were characterized by X‐ray diffractometry (XRD) which showed the intercalated structure of nanoclay in the matrix. Thermal stability of the samples was studied using Thermogravimetric Analysis (TGA), and the degradation kinetic parameters were determined using various methods including Kissinger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
1
7
0
9
Order By: Relevance
“…An enhancement in the compressive modulus of porous PCL/clay nanocomposites was previously reported by Liu et al12 who found that by premixing PCL with 5 wt % DK2 (3.5 wt % clay platelets)40 followed by the addition of ADC the modulus of the porous PCL increased by ∼ 60%, while the specific compressive modulus presented an increase of close to 10%. At 5.8 wt % ADC‐treated clay (i.e., 2.2 wt % clay platelets‐calculated according to the equations presented in the Supporting Information section), we discovered that by pretreating the organoclay (C30B containing the same surfactant as that of DK2) with the blowing agent, the compressive modulus increased by 152%, while the specific compressive modulus was enhanced by 69%, compared to the pristine porous PCL(ADC).…”
Section: Resultssupporting
confidence: 64%
“…An enhancement in the compressive modulus of porous PCL/clay nanocomposites was previously reported by Liu et al12 who found that by premixing PCL with 5 wt % DK2 (3.5 wt % clay platelets)40 followed by the addition of ADC the modulus of the porous PCL increased by ∼ 60%, while the specific compressive modulus presented an increase of close to 10%. At 5.8 wt % ADC‐treated clay (i.e., 2.2 wt % clay platelets‐calculated according to the equations presented in the Supporting Information section), we discovered that by pretreating the organoclay (C30B containing the same surfactant as that of DK2) with the blowing agent, the compressive modulus increased by 152%, while the specific compressive modulus was enhanced by 69%, compared to the pristine porous PCL(ADC).…”
Section: Resultssupporting
confidence: 64%
“…However, the HDT values observed for B2, U3, and C3 increased 54%, 220%, and 195% as compared with Epoxy/UP system. This is due to the synergistic effect between Epoxy/UP and nanoclay can lead to an improved mechanical and thermal stability, by ease of exfoliation of nanoclay and the formation of Epoxy/UP/C30B nanocomposites . This is attributed to prove a synergetic effect of sisal fibers and C30B clays in heat deflection temperature of Epoxy/UP matrix which allow the mobility of the resin chains resulting increased in the intensity of the tan delta peaks.…”
Section: Resultsmentioning
confidence: 99%
“…PC/ABS blend nanocomposites have been chosen as a research object because of their wide use in numerous structural applications in civil engineering and transport. Besides it, in most of the previous researches on PC/ABS blend -nanoclay nanocomposites [12][13][14][15][16][17][18][19][20], generally experimentally determined results on the structure as well as rheological, mechanical, thermal and sorption properties have been analysed without trying to apply real theoretical analysis of elastic properties, which is under the scope of this study.…”
Section: Introductionmentioning
confidence: 99%